Implementasi Peraturan Menteri Sosial Nomor 1 Tahun 2018 Tentang Program Keluarga Harapan (PKH) - Ade Irma Pratiwi; Ahmad Ahmad (QAIMUDDIN: Journal of Constitutional Law Review, 2022)
The research entitled Implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Hope Family Program aims to answer several problem formulation. This research was conducted in Lalowosula Village, Ladongi District, East Kolaka Regency. Data obtained through observation data, interviews with several informants and supported by secondary data. Data analiysis method used through data reduction, data presentation and drawing conclusion. The results of this study indicate that the implementation of the family of hope program in the village of lalowosula has not run optimally due to things that have not been fulfilled in its application. Organization of the family of hope program in East Kolaka Regency has formade its management both at the sub-district and village/village levels. The interpretation of the implementation of the family of hope program in the kolaka timur district in general and the village or lalowosula in particular refers to the standard operating procedures that have been determined by the Ministry of Social Affair. The application shows that the implementation of the family of hope program in the village of lalowosula has not run optimally